Penatalaksanaan Fisioterapi Pada Kasus Fraktur 1/3 Distal Radius Sinistra Di Rsud Dr. Harjono Ponorogo - Dewi, Fanisa Rahma, Sugiono, S.Fis., M.H (Kes) (2016)
Background: Conditions 1/3 radius fractures would cause the problems that edema, pain, limitation of movement, and impaired daily activities such as eating, wearing clothes, toiletries, and others. Physiotherapy very important role in addressing the problems of post fracture, by providing exercise therapy is static contracion, hold relax and ressisted active movement. In this exercise aims to maintain range of motion, reduce pain, reduce swelling, improve the range of motion. Purpose: To determine the therapeutic benefit of exercise in improving range of motion and increase muscle strength in patients with fractures of the radius of 1/3 in dr. Harjono Ponorogo Results: There are a result of a decrease in tenderness of To = 0.3 becomes T6 = 0 , painful motion of To = 1.2 to T6 = 0.5 . The resulting increase in the left wrist of active LGS To = S ( 15˚ -0˚- 20˚ ) , F ( 20˚- 0˚- 15˚ ) into T6 = S ( 50˚- 0˚- 25˚ ) , F ( 30˚- 0˚ -30˚ ) and increased passive LGS The left wrist of To = S ( 30˚- 0˚- 20˚) , F( 20˚-0˚-15˚) became T6 = S ( 50˚-0˚-40˚ ) , F = ( 45˚-0˚-40˚). The decrease edema of the left wrist To 47 cm to 45 cm. Iincrease Activity Daily Living (ADL) results of examination of functional ability to get the value of 30% means that the patient has a disability / dependency light. Conclusion: Treatment with modalities Infrared physiotherapy and exercise therapy can reduce pain and stiffness in the hands of patients and to improve the range of motion and increase muscle strength in patients with fractures of the radius of 1/3 in dr. Harjono Ponorogo.